Power System Stability and Robustness of Synchronous Machine’s Excitation Control with Magnitude-Phase Voltage Regulator - Butkevych, O.F.; Agamalov, O.M. (Технічна електродинаміка, 2014)
The conditions necessary to provide the robust stability and robust control of synchronous machine’s excitation control with magnitude-phase automatic voltage regulator are determined.